Reference Values for Pulmonary Single-Breath Diffusing Capacity – Results of the “Study of Health in Pomerania” - Bollmann, T.; Ittermann, T.; Gläser, S.; Völzke, H.; Doerr, M.; Habedank, D.; Obst, A.; Ewert, R.; Schäper, C.; Stubbe, B. (Pneumologie, 2020)
Objectives The assessment of pulmonary single-breath diffusing capacity is a frequently performed diagnostic procedure and considered as an important tool in medical surveillance examinations of pulmonary diseases.The aim of this study was to establish reference equations for pulmonary single-breath diffusing capacity parameters in a representative adult-population across a wide age range and to compare the normative values from this sample with previous ones.Methods Diffusing capacity measurement was carried out in 3566 participants (1811 males) of a cross-sectional, population-based survey (“Study of Health in Pomerania – SHIP”).Results Individuals with cardiopulmonary disorders and current smoking habits were excluded, resulting in 1786 healthy individuals (923 males), aged 20 – 84 years. Prediction equations for both sexes were established by quantile regression analyses, taking into consideration the influence of age, height, weight and former smoking.Conclusion The study provides a novel set of prediction equations for pulmonary single-breath diffusing capacity in an adult Caucasian population. The results are comparable to previously reported equations, underline their importance and draw attention to the need for up-to-date reference equations that adequately take into account both the subjects’ origin, age, anthropometric characteristics and the equipment used.